Atavistic identity in bilingual rural space students in the Aymara Altiplano of Ilave (Revista Innova Educación, 2020)
The summary of configuration of cultural atavistic identity, finds a significant space in Aymara students who go through moments of sociocultural and educational syncretism in the surandine spectral region of Peru. The objective is channeled in determining the level of atavistic identity in bilingual students of the rural area in the Aymara Highlands of Ilave. The study corresponds to the quantitative approach of a descriptive nature and the technique used was the structured survey with their respective questionnaires that served as an instrument for the survey of objective information, taking as a population universe 138 original students. In conclusion, 58% of students maintain the traits of cultural atavistic identity by the practice of their beliefs, customs, traditions and because they do not neglect their original culture, even if it is constantly threatened by hegemonizing cultures from the West.
Keywords: Cultural identity; tradition; bilingual education; Aymaras; education